Policy Implementation in Carrying Out Forest and Land Rehabilitation in Seteluk District, West Sumbawa Regency - Jaya, Indra; Zulkieflimansyah, Zulkieflimansyah; Yamin, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Forest and land rehabilitation is one effort that can be made to overcome this problem. Mining activities always have positive and negative impacts. The positive impact is to spur the country's economic prosperity, while the negative impact is the emergence of environmental damage. The objectives of this research are: 1) to describe the implementation of Forest and Land rehabilitation policies in Seteluk District, West Sumbawa Regency. This research uses descriptive research with a qualitative approach, data collection techniques through interviews, observation and documentation, with key informants such as the Head of the West Sumbawa Regency LHK service, the Secretary of the Seteluk Sub District office, the Head of Kelanir Village, the head of Meraran Village. The research results show that the implementation of the Barapan Kebo cultural tourism promotion policy by the Regency government is in accordance with the policy implementation indicators according to Edward III, namely: 1) Communication, 2) Resources, 3) Disposition, 4) Bureaucratic Structure. Meanwhile, inhibiting factors are regulations, network development and funding. Community participation includes 1) planning role, 2) implementation role, 3) monitoring role, 4) evaluation role.